A multi-cultural study on perceived social support and resilience towards academic stress among international students during covid-19 - Sania Aziz; Winarini Wilman D. Mansoer; Ifdil Ifdil (Universitas Negeri Padang, 2022)
The current study aimed to see the correlation of perceived social support in enhancing resilience in international students towards academic stress and COVID-19 stress. Extend to which the coronavirus COVID-19 pandemic is affecting worldwide. This study explores social support and resilience towards academic stress and COVID-19 stress in international students—the sample of 83 International Asian and African students, respectively taken from different Countries and universities. The results revealed a significant effect of perceived social support and resilience towards COVID-19 stress. However, further results showed there was a non-significant relationship between perceived social support, resilience towards academic stress.